2014
DOI: 10.1093/fampra/cmu007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary counselling for cardiovascular disease prevention in primary care settings: results from a German physician survey

Abstract: The data showed high levels of involvement by German PCPs in CVD prevention and dietary counselling. The rather low perceived success of dietary intervention and differences with respect to patients' health insurance status indicate a need to address both communication skills in medical training and appropriate reimbursement of preventive services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 12 publications
1
19
0
6
Order By: Relevance
“…GPs clearly stated that their focus was not primary prevention but secondary prevention at best. Such findings have been shown by other survey studies in a German GP population [38]. The focus group participants in our study considered carefully when, and whether or not, to include primary preventive efforts in relation to the GP-specific patient-doctor relationship and their self-perceived role as a GP.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…GPs clearly stated that their focus was not primary prevention but secondary prevention at best. Such findings have been shown by other survey studies in a German GP population [38]. The focus group participants in our study considered carefully when, and whether or not, to include primary preventive efforts in relation to the GP-specific patient-doctor relationship and their self-perceived role as a GP.…”
Section: Discussionsupporting
confidence: 68%
“…It is very likely that respondents were highly interested in primary prevention resulting in a responder bias such that non-responders are less likely give primary prevention advice to their patients. Other studies have found female physicians in Germany to be more active in providing lifestyle counseling to patients, especially on dietary habits, which reiterates that our sample was more prone towards primary prevention than the general population of GPs in Germany [38]. Response rates to physician surveys are generally low, especially when no compensation is given.…”
Section: Discussionmentioning
confidence: 54%
“…Participant numbers for all studies ranged from 3 to 4074; most were between 47 and 1136 with the exception of one larger study (44). All studies were published between the years 2012 and 2018.…”
Section: Descriptive Findingsmentioning
confidence: 99%
“…Health professionals are under the impression that media are the most important source of information about what a healthy dietary pattern is for the population (28). Patients demand nutritional education but 78.5% of physicians consider that they do not have the necessary training to give good nutritional advice (29).…”
Section: What Is the Role Of Primary Physicians?mentioning
confidence: 99%